A single molecule view of FEN1 remarkable substrate recognition, perfect catalysis and regulation - Zaher, Manal (2019)
DNA replication is one of the most fundamental processes in all living organisms. Its semi-discontinuous nature dictates that the lagging strand is synthesized in short fragments called Okazaki fragments. In eukaryotes, each Okazaki fragment is initiated by an ~ 30-40 nucleotide-long RNA-DNA hybrid primer that is synthesized by Pol α-primase complex. To ensure genomic stability, the RNA primer has to be excised, any misincorporations by Pol α have to be corrected for and finally the resulting nick has to be sealed generating a contiguous strand. This feat is accomplished by a highly coordinated and regulated process called Okazaki fragment maturation. At the center of this process are 5’ nucleases, which are structure-specific nucleases that catalyze the incision of phosphodiester bonds one nucleotide into the 5’ end of ssDNA/dsDNA junctions. Previous structural and biochemical studies have shed some light on the mechanism of FEN1 substrate recognition, its catalysis and regulation. However, many gaps in our understanding of this remarkable nuclease still persist. Moreover, the choice between the short- and long-flap pathways is still elusive. Finally, the mechanism of the coordination among the different enzymatic activities of the polymerase, the nuclease and the ligase during Okazaki fragment maturation is still debatable. In this work, we set out to study FEN1 substrate recognition, catalysis and regulation using single molecule techniques. We show that FEN1 employs a sophisticated substrate recognition mechanism through which it actively distorts the DNA to ~100˚ bent angle. It also displays a remarkable selectivity towards its cognate substrate and avoids off-target substrate by a lock-down mechanism that commits the enzyme for catalysis on cognate substrates while promoting the dissociation of non-cognate substrates. We further characterized FEN1 reaction from substrate binding/bending to product handoff and built a comprehensive kinetic scheme that shows FEN1 releasing its product in two steps. Finally, we uncovered an unprecedented role of FEN1 in the choice between short- and long-flap pathways.